Reflexiones escépticas, principiológicas y económicas sobre el consentimiento necesario para la recolección y tratamiento de datos - Santos Divino, Sthéfano Bruno (2019)
Is there a correspondence or affinity between the juridicalprincipiological and factual-economical conceptions for the effective protection of the consent of the holder of personal data when hiring in a network?Under the mantle of the present question, it aims to analyze the contemporary contractual scenario under the perspective of the privacy policy and the Brazilian General Data Protection Law (LGPD). In this context, it is proposed a skeptical reflection on the principles and economic guidelines defended by law and doctrine to verify if the consent is an instrument of real effectiveness to the tutelage of the subjects in network. The first topic concerns the conceptual and conceptual analysis of consent in the LGPD and in the specialized doctrine. The second topic deals with the limited rationality of the users of the network services in understanding the dispositions in the policies of privacy and in the terms of electronic services. At the end, it is concluded that despite the juridical and legal defense aimed at solidifying consent as an indispensable tool for collecting and processing data, the current electronic contractual model does not allow its effective concretization, proposing, in this case, an alternative. The rationale is anchored in the deductive, bibliographical and integrated research methods and in the case study technique.